Ultimate warrior workouts : fitness secrets of the martial arts - Rooney, Martin, 1971- (New York : Harper, 2010)
The author recounts his experiences training with masters of the main disciplines in the mixed martial arts--Brazilian jiu jitsu, muay thai, wrestling, boxing, judo, kickboxing, sambo, and karate--and recommends a related fitness program.
The mixed martial arts of MMA. An overview of martial arts history. Brazilian Jiu Jitsu. Muay Thai. Wrestling. Boxing. Judo. Kickboxing. Sambo. Karate -- Training programs. Warrior performance nutrition. Warrior cardio training. Warrior flexibility training. Partner-based training. Warrior workouts.
Keywords: Mixed martial arts; Physical fitness; Mixed martial arts; Physical fitness; Budo; Nonfiction